COMPARISON OF RECURRENCY OF BENIGN PAROXYSMAL POSITIONAL VERTIGO WITH AND WITHOUT HYPERTENSION - Kiki Mohammad Iqbal (International Journal of Research Science and Management, 2020)
Background: Benign paroxysmal positional vertigo (BPPV) is the most common vestibular disorder. Several studies have shown that comorbid hypertension can affect the prognosis of BPPV. This study aims to assess the comparison of BPPV patient recurrences with and without hypertension. Method: This research is an analytical study with a cohort design. The research was conducted at the Neurology Polyclinic of RSUP Haji Adam Malik Medan for the period of October 1, 2019 to December 1, 2019. A total of 40 BPPV patients with and without hypertension were taken into the study sample, using consecutive sampling technique. For 7 days recurrence was recorded and on the 7th day, BPPV symptoms were reassessed with the DixHallpike maneuver. Furthermore, statistical analysis was performed using the Mann Whitney U test and the Kruskall Wallis test. Result:Of the 40 research subjects, there were 29 more women (72.5%) and the highest age was in the range >40 - 60 years as many as 23 subjects (57.5%). There were 18 people (90.0%) BPPV patients with hypertension and as many as 4 people (20.0%) BPPV patients without hypertension experienced recurrences, where one recurrence was found in 13 people (65.0%) and more than one recurrence. times or vertigo was felt continuously found in 5 people (25.0%) BPPV patients with hypertension (p = 0.000). Conclusion: There is a significant difference in recurrence between BPPV patients with and without hypertension